Molecular Typing of Malassezia and Histoplasma in Bronchoalveolar Lavage Fluid from Patients with Pulmonary Respiratory Infections - Zahraa Muhyi Al Shareefy1 , Zaidan Khlaif Imran2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Pulmonary infections caused by fungal infection is one of the generality serious lung disease. Its symptoms and risk vary from controlled to fatal if not treated early. The aim study isolation and identification of Histoplasma and Malassezia inhabitant lung of patients pulmonary respiratory infections. A total of 103 clinical samples were collected from the patients who attenuated the Thoracic and Respiratory Diseases Center, Tebba National Hospital and Morjan Educational Hospital in Babylon province . The samples were taken under the supervision of the physician after diagnosis of pulmonary diseases such as Tuberculosis , Pulmonary fibrosis , lung cancer , asthma , Thoracic Allergy. Lop full of bronchoalveolar lavage fluid (BAL) were Direct cultured on Sabouraud’s Dextrose Agar (SDA), microscopically and molecular identification was performed based on used specific primer pairs for Histoplasma and Malassezia. The results shown identification many yeast and molds based on cultural and molecular assay shown: A 438 out of 500 isolates of yeast were identified as Candida spp. , 27 isolates of Malassezia spp. and other filamentous fungi such as Zasmidium cellare, Aspergillus spp. , Penicillium spp. , Fusarium spp. , Mucor sp., Alternaria spp., Acremonium sp. and Cochliobolus kusanoi .